Microalgae: Promising solutions paving the way toward a greener and more sustainable future - Qin, Yunhan; Li, Tingfu; Nie, Changliang; Geng, Xueyun; Sun, Xiaomin (Frontiers in Fuels, 2025)
Microalgae represent a promising solution for achieving greener and more sustainable applications, owing to their rapid growth rates, high photosynthetic efficiency, and capacity to produce valuable compounds such as lipids. Biofuels based on microalgae have emerged as a promising alternative to fossil fuels due to their sustainable and renewable nature. Moreover, the use of microalgae cultivated in wastewater not only contributes to biofuel production but also provides additional benefits such as wastewater treatment and CO2 sequestration to realize the carbon neutrality. However, the commercial viability of microalgae-based biofuels remains uncertain. This article reviews advancements in microalgae-based sustainable production while exploring its multi-objective applications beyond energy generation. Multi-objective applications, including multi-algal systems, species development, process optimization, and dust suppressant are necessary to improve cost-effectiveness and enhance overall feasibility.